Evasion at the Federal Institute of Espírito Santo campus Itapina: case study of the profile, relevant factors and proposed instrument for follow-up. (Revista Educação, Artes e Inclusão, 2024)
School dropout consists when student’s leaves their cousers without conclud. This paper aimed to discuss the reasons that led students from 2014 to 2016 to evade the undergraduate degree in Agricultural Sciences of the Federal Institute of Espirito Santo. This research aimed to investigate possible reasons for dropout that may be internal to the institution and those linked to the personal situations of alumni. We opted for exploratory research of qualitative nature, using tools for data collection and analysis quantitatively and qualitatively, in addition to the participatory observation methodology. In the technical procedures, a questionnaire with objective questions was applied, based on the current questionnaire used to measure the dropout of the institution's students. According to the answers obtained, we infer that the main reasons that led the students to drop out were the poor recognition of the teaching profession, dissatisfaction with the content and chosen course, dissatisfaction with their academic performance, etc. It should be noted that some of the above answers disagree with the fact that the highest dropout rates occur in the first semesters, showing that the poor persistence or support to the student during the course can also be a determining factor.
Keywords: school abandonment; permanence and success; college education